Biopsychosocial background of knowledge sharing: contributions of Social Exchange Theory to knowledge management - Pinheiro de Souza, Leonardo Pereira [UNESP]; Silva, Rafaela Carolina da [UNESP]; Gomes de Mello, Mariana Rodrigues [UNESP]; Zago Junior, Paulo Henrique [UNESP]; Bassan de Moraes, Cassia Regina [UNESP] (Univ Federal Rio Grande Sul, Fac Biblioteconomia & Comunicacao, 2022)
In a hyper-competitive and information-intensive marketing context, managing knowledge is vital. Knowledge is a creation of the human mind and represents symbolic power for its holder, resulting in the need for motivation to share it. The Social Exchange Theory deals with the mechanisms involved in the exchange of benefits between subjects, highlighting reciprocity, group benefits and even altruism as motivators. While Philosophy discusses egocentric interests in the relationship between the subject and the collectivity, biology shows altruism as the key to evolutionary success. The human psyche is complex, admitting the coexistence of cooperation and competition in knowledge sharing. It is aimed to unveil what motivates humans to share knowledge, investigating the configurations and the most highlighted aspects in academic literature about the interaction between the Social Exchange Theory and Knowledge Management. As methodological procedures, a search was carried out in the Scopus database on the interaction between Social Exchange Theory and Knowledge Management, performing a keywords co-occurrence analysis with VosViewer software and, finally, a qualitative analysis was performed, concerning to the meaning of the most relevant keywords, through the most cited articles. As a result, the keywords with greater affinity were grouped, highlighting the most used terms in each group for reading and summarizing the most cited papers that contained them. The most cited papers show the need to create motivational strategies, creating a suitable environment for knowledge sharing, mitigating the fear of personal power loss as a consequence of this sharing.
Keywords: Social Exchange Theory; knowledge management; competition; cooperation; knowledge sharing